If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(x + -3) + 3 = -15 Reorder the terms: 9(-3 + x) + 3 = -15 (-3 * 9 + x * 9) + 3 = -15 (-27 + 9x) + 3 = -15 Reorder the terms: -27 + 3 + 9x = -15 Combine like terms: -27 + 3 = -24 -24 + 9x = -15 Solving -24 + 9x = -15 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '24' to each side of the equation. -24 + 24 + 9x = -15 + 24 Combine like terms: -24 + 24 = 0 0 + 9x = -15 + 24 9x = -15 + 24 Combine like terms: -15 + 24 = 9 9x = 9 Divide each side by '9'. x = 1 Simplifying x = 1
| (10+5)*(30+6)=15+36 | | -6x-7x+4=5 | | 21(n+22)=945 | | N-1-3=-1 | | 2m+4n=12 | | 7(7r+19)=7-14r | | 12x+3=-10 | | -8x+4x+6x=-6 | | -12x+2y=-14 | | 3(7h-15)=9+18h | | -7(7-3x)=-175 | | 16x+8=-3 | | q/8-5=9 | | -17w+7(17w+12)=18w | | 5x+2-6x=-11 | | 702/u=27 | | 18.94+15.8g=-3(-18.8g+11.28) | | a-42=-4a-7 | | 5(8+2x)=-30 | | -2x+4-2x=-12 | | 18.94-15.8g=-3(-18.8g+11.28) | | 5+5d=80 | | 7r+3-3r=15 | | X-5+9x=40 | | z^2+(12+6i)z+(11+24i)=0 | | 80=18+2p | | 2x+9+4x=-57 | | 4.3f-14.65-19.08=-3.13+12.8f | | -x+2x+5+2x=-25 | | 6n^2-18n-18=-6 | | 9v-17=73 | | 2[5x+8]=6x+20 |